Use of sorghum seed tissue as a biocatalyst in a stirred reactor for oxalic acid determination - Fernandes, João Roberto [UNESP]; De Oliveira Neto, Graciliano; Kubota, Lauro T.; Tubino, Matthieu (Royal Society of Chemistry (RSC), 1996)
The enzyme oxalate oxidase, E.C. 1.2.3.4 from Sorghum vulgare seeds (variety BR303) was used to develop a new sensor for oxalate determination without any purification. The sorghum seeds were conditioned in a 0.10 mol I-1 KCl solution. Then, these seeds were put in a stirring bar type enzymic reactor and coupled with an electrode for CO2. This device was introduced into a cell containing 10.0 ml of a 0.10 mol I-1 KCl solution saturated with oxygen. This sensor showed a linear response between 1.0 and 4.0 × 10-3 mol I-1 with a slope of 30 mV per decade of oxalate concentration at 25.0°C. The sensor was stable for one month or 200 determinations. The response time was about 60 s. The Michaelis-Menten constant determined for this enzyme was 1.5 × 10-3 mol I-1.